Gibran Language Style in Indonesian Vice-Presidential Election Debate 2024 - Asri, Delukman; Hasim, Fiviyanti (Inspiring: English Education Journal, 2025)
Many people talked about Gibran’s step to be a vice president. The Constitutional Court changed some rules for vice president before Gibran was declared as Prabowo’s vice president candidate which head of court is his uncle. The national committee of general election presented vice president debate which each candidate will show the ideas or attack other candidates’ statement. This research used stylistics in identifying Gibran’s language style. The researcher writes the words, phrases and sentences in six segments from youtube with title “RONDE 4! Debat Cawapres 2024. The result indicates that Gibran used repetition, alliteration and anti-climax repeating his ideas. Then, he used satire, cynicism and rhetoric attacking his opposite candidates. Gibran described his programs strongly and explained his ideas assertively. Candidate’s style in this debate is very important for make sure that the voters get the ideas and understanding the candidate’s standing point.